Oral NAloxone to overcome the moRphine effect in acute COronary syndrome patients treated with TICagrelor — NARCOTIC trial - Niezgoda, Piotr; Barańska, Malwina A.; Sikora, Joanna; Sobczak, Przemysław; Buszko, Katarzyna; Sikora, Adam; Marszałł, Michał P.; Navarese, Eliano P.; Jilma, Bernd; Kubica, Jacek (Cardiology journal, 2022)
Numerous worldwide clinical trials have proven the indisputably negative influence of morphine on the pharmacokinetics and pharmacodynamics of P2Y12 receptor inhibitors in patients presenting with acute coronary syndromes. The aim of this trial was to evaluate whether oral coadministration of an anti-opioid agent, naloxone, can be considered a successful approach to overcome 'the morphine effect'. Consecutive unstable angina patients receiving ticagrelor and morphine with or without orally administered naloxone underwent assessment of platelet reactivity using Multiplate analyzer as well as evaluation of the pharmacokinetic profile of ticagrelor and its active metabolite, AR-C124910XX, at 9 pre-defined time points within the first 6 hours following oral intake of the ticagrelor loading dose. The trial shows no significant differences regarding the pharmacokinetics of ticagrelor between both study arms throughout the study period. AR-C124910XX plasma concentration was significantly higher 120 min after the ticagrelor loading dose administration (p = 0.0417). However, the evaluation of pharmacodynamics did not show any statistically significant differences between the study arms. To conclude, this trial shows that naloxone co-administration in ticagrelor-treated acute coronary syndrome patients on concomitant treatment with morphine shows no definite superiority in terms of ticagrelor pharmacokinetic and pharmacodynamic profile.